Application Of Restorative Justice In Narcotics Crime Cases - Lidya Rahmadani Hasibuan (Yayasan Multidimensi Kreatif, 2024)
The problem of narcotics (narcotics, psychotropic substances and other addictive substances) is a special crime whose problem spreads nationally and internationally, because its abuse has a negative impact on the lives of society, nation and state. The role of law in this case is to overcome crime through criminal law policy and is one of the efforts in law enforcement. The aim of the research is to determine the Juridical Review of the Implementation of Rehabilitation Institutions at the Prosecution Stage by Prosecutors in Criminal Cases of Narcotics Abuse. Understand the application of Rehabilitation Institutions in the prosecutor's prosecution stage for narcotics abuse through rehabilitation based on Attorney General's guidelines No.18 of 2021. Imprisonment for victims of narcotics abuse, especially children, is a deprivation of liberty and contains a negative side so that the purpose of punishment cannot be realized optimally. Meanwhile, rehabilitation is intended so that people who are categorized as addicts are free from their dependence. Completion of the handling of criminal cases of narcotics abuse through rehabilitation is carried out by prioritizing restorative justice and expediency (doelmatigheid), as well as considering the principles of fast, simple and low-cost justice, the principle of criminal justice as a last resort (ultimum remedium), cost and benefit analysis, and recovery of the perpetrator